Traumatic pseudoaneurysm of the superficial temporal artery (Indian Journal of Case Reports, 2019)
Pseudoaneurysm is deficit of all the 3 layers of the blood vessel. Superficial temporal artery due to its course is more prone for trauma and 95% of the pseudoaneurysm of the superficial artery is due to trauma. Here, we report the case of a traumatic pseudoaneurysm of the superficial temporal artery in a 19-year-old patient. The patient came with the complaints of swelling in the left side of the forehead for 3days and a history of trauma 3 days back by a cricket ball. A duplex scan showed a pseudoaneurysm of the superficial temporal artery. Surgical excision of the aneurysm was done after ligating proximal and distal pedicles. Digital subtraction angiography is the gold standard investigation, but duplex would be enough in most of the cases for diagnosingand surgical excision after ligating the proximal and distal pedicles is the treatment of choice.